Permanent magnet synchronous motor control performed using PI-backstepping with a model of harmonics reduction - Mohamed El Ghmary; Youssef Agrebi Zorgani; Said Ziani (Institute of Advanced Engineering and Science, 2023)
This paper focuses on the control of permanent magnet synchronous motors (PMSMs) utilizing a non-linear adaptive PI-Backstepping design and a model of harmonics reduction approach that uses an active shunt filter followed by a cascade bandpass filter. While conventional backstepping may assure the system's stability, it is often imprecise. It creates a significant amount of static error, which has a detrimental effect on the system's behavior, such as disruptions and loads that might arise in industrial settings. We can assure minimum fixed errors and considerable interaction with uncertainty by integrating the PI controller with adaptive backstepping through robust Lyapunov functions. Numerical simulations are used to demonstrate the proposed controller's effectiveness.